Finalist for the Harry Otten Award in Innovation in Meteorology - Charalambides, Alexandros G. (My University, 2026)
The work carried out with Dr Takapis (then PhD student) was a finalist for the Harry Otten Award in Innovation in Meteorology
Keywords: Sciences